Analisis Kualitas Pelayanan Terhadap Kepuasan Pengunjung Di Taman Mini Indonesia Indah - Shofi Dhiya Ulhaq; Nabila Sri Astuti; Jihan Fadillah; Rizki Sholehudin Yusuf; Liliana Dewi (CV. Syntax Corporation Indonesia, 2021)
This study discusses the quality of service on visitor satisfaction at Taman Mini Indonesia Indah. In this study there are two indicators, service quality as the independent variable and visitor satisfaction as the dependent variable. The method used in this study is a quantitative type in order to determine the quality of service to visitor satisfaction by using primary data, observations, questionnaires and literature review to complete this research. Based on the results of this study, the quality of service consisting of tangible, empathy, responsiveness, responsibility, and assurance has a significant influence on visitor satisfaction, namely the influence of service quality on visitor satisfaction with the known t value of 21,214 > t table 1,664, so it can be concluded that the value of Service Quality (X) affects the Visitor Satisfaction variable (Y)